Antibiotic Susceptibility of Bacterial Agents Causing Meningitis in Children Older than 1 Month - Mohsenipour, Reihaneh; Gharib, Behdad; Eshaghi, Hamid; Rahmani, Parisa (Drug Research, 2020)
The frequency and antibiotic susceptibility of bacterial meningitis in children older than one month at Children's Medical Center during 2012–2017 were evaluated in this study. The CSF samples were cultured, and antibiotic sensitivity tests were performed. The samples were cultured on chocolate agar, blood agar (for gram positive) and Mkanky (for gram negative). The antimicrobial susceptibility of the isolates was determined using the disc diffusion method. In total, 72 samples were positive for bacterial infection where Staphylococcus epidermidis (20.8%) was seen most and Enterobacter (1.4%) and Pseudomonas aeruginosa (1.4%) was seen least. Most of these patients were under 1 year of the age and overall frequency of positive cultures of CSF in men (58.3%) was greater than women (41.7%). Bacterial meningitis has relatively diverse etiological factors that include; time of infection, geographical location and age. Most commonly seen bacteria were Staphylococcus aureus with S.epidermidis whereas, Escherichia coli and Pseudomonas aeruginosa was seen least. This result can be substantial in hospitalized patients, because these bacteria are also the result of nosocomial infections.
Keywords: bacterial meningitis; children; antibiogram